Effects of inclination angle and non-uniform heating on mixed convection of a nanofluid filled porous enclosure with active mid-horizontal moving - Nithyadevi, N.; Begum, A. Shamadhani; Öztop, Hakan Fehmi; Al-Salem, Khaled (Pergamon-Elsevier Science Ltd, 2017)
Inclination angle effects on mixed convection heat transfer in a rectangular porous enclosure filled by Cu-water nanofluid have been numerically analyzed in the present study. Boundary of the enclosure has sinusoidal heating vertical walls, adiabatic horizontal walls and the heated mid-horizontal moving wall. Control volume method is used to discretize the nonlinear governing differential equations. Richardson number (Ri) from 0.01 to 100, Darcy number (Da) from 10(-3) to 10(-5), inclination angle (gamma) from 0 degrees to 90 degrees, solid volume fraction of nanoparticle (phi) from 0.0 to 0.2 and porosity (epsilon) of the porous medium from 0.4 to 0.8 are discussed and portrayed in the form of streamlines, isotherms, average Nusselt number and velocity graphs. It is observed that the governing flow parameters has significant impact on the fluid flow and temperature distributions. In particular, the features of enclosure inclination, presence of copper nanoparticles in the fluid-saturated porous media and inserting moving wall at the centre of the enclosure are found to enhance the heat transfer rate. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Inclination; Mixed convection; Nanofluid; Porous medium; Sinusoidal heating